Phraséologie et programmation neurolinguistique : le rôle des phrasèmes dans la reconfiguration cognitive et discursive du sujet. - ZRIGUE, ANISSA (Nouvelles Perspectives en Sciences Sociales, 2026)
This article examines the role of phrasemes in the cognitive and discursive reconfiguration of the subject, particularly within neuro-linguistic programming (NLP) practices. Long considered peripheral lexical units, fixed expressions, proverbs, and discourse routines are now acknowledged as central devices that contribute to cultural anchoring, language learning, and cognitive structuring. NLP employs these stereotyped formulas to influence mental representations, emotions, and behavior, providing an ideal context for exploring the relationship between linguistic fixity and cognitive plasticity. This study offers a phraseological analysis of NLP formulas, highlighting their syntactic stability, illocuto-perlocuto function, and axiological orientation. It shows that phrasemes are not merely frozen structures but linguistic instruments of subjectivation, capable of reshaping discourse and self-perception.